2015
DOI: 10.1194/jlr.m054882
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of ANGPTL3 reduces hepatic VLDL-triglyceride secretion

Abstract: This article is available online at http://www.jlr.org an enzyme that catalyzes an early step in cholesterol biosynthesis, effectively lower plasma LDL-C levels and prevent CHD ( 2 ). Human genetic studies have provided several new targets for LDL-C lowering. Individuals who lack ApoB ( 3 ), or microsomal transfer protein (MTP), the enzyme that transfers TG to TG-rich lipoproteins in the liver and intestine ( 4 ), have very low LDL levels. Agents that suppress ApoB expression ( 5 ) or inhibit MTP activity ( 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
130
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(148 citation statements)
references
References 57 publications
(57 reference statements)
11
130
3
4
Order By: Relevance
“…The reductions achieved correlated with baseline lipid levels. Similar results have been reported with evinacumab (REGN-1500), an antibody-based inhibitor of ANGPTL3 [62]. A dose-ranging study of evinacumab in three patients with HoFH showed it could reduce LDL-C by 46% [63].…”
Section: Aso Therapy To Angiopoetin-like Protein-3 (Angptl3)supporting
confidence: 78%
“…The reductions achieved correlated with baseline lipid levels. Similar results have been reported with evinacumab (REGN-1500), an antibody-based inhibitor of ANGPTL3 [62]. A dose-ranging study of evinacumab in three patients with HoFH showed it could reduce LDL-C by 46% [63].…”
Section: Aso Therapy To Angiopoetin-like Protein-3 (Angptl3)supporting
confidence: 78%
“…In fact, the attenuated postprandial lipemia together with reduced flux of FFAs directed to the liver may explain the lower VLDL secretion rate and fasting TG reported in homozygous FHBL2 (13) and recently confirmed during antibody-mediated inhibition of ANGPTL3 (48). Moreover, the faster hepatic removal of remnants may decrease the fraction that is converted in circulation into LDL, thereby lowering LDL production and fasting LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.001 for comparison between homozygous subjects and controls; † P < 0.001 for comparison between homozygous and heterozygous subjects; and ‡ P < 0.001 for comparison between heterozygous subjects and controls. FFAs (48). More detailed tracer studies are needed to clarify the role of ANGPTL3 in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for the LDL-lowering effect of ANGPTL3 is currently not clear, but appears not to involve the major canonical pathways of clearance of ApoB-containing lipoproteins ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%